The Role of Sink Strength and Nitrogen Availability in the Down-Regulation of Photosynthetic Capacity in Field-Grown Nicotiana tabacum L. at Elevated CO2 Concentration - Ruiz-Vera, Ursula M.; De Souza, Amanda P.; Long, Stephen P.; Ort, Donald R. (Frontiers in Plant Science, 2017)
Down-regulation of photosynthesis is among the most common responses observed in C3 plants grown under elevated atmospheric CO2 concentration ([CO2]). Down-regulation is often attributed to an insufficient capacity of sink organs to use or store the increased carbohydrate production that results from the stimulation of photosynthesis by elevated [CO2]. Down-regulation can be accentuated by inadequate nitrogen (N) supply, which may limit sink development. While there is strong evidence for down-regulation of photosynthesis at elevated [CO2] in enclosure studies most often involving potted plants, there is little evidence for this when [CO2] is elevated fully under open-air field treatment conditions. To assess the importance of sink strength on the down-regulation of photosynthesis and on the potential of N to mitigate this down-regulation under agriculturally relevant field conditions, two tobacco cultivars of strongly contrasting ability to produce the major sink of this crop, leaves, (Nicotiana tabacum L. cv. Petit Havana; cv. Mammoth) were grown under ambient and elevated [CO2] and with two different N additions in a free air [CO2] (FACE) facility. Photosynthetic down-regulation at elevated [CO2] reached only 9% in cv. Mammoth late in the season likely reflecting sustained sink strength of the rapidly growing plant whereas down-regulation in cv. Petit Havana reached 25%. Increased N supply partially mitigated down-regulation of photosynthesis in cv. Petit Havana and this mitigation was dependent on plant developmental stage. Overall, these field results were consistent with the hypothesis that sustained sink strength, that is the ability to utilize photosynthate, and adequate N supply will allow C3 crops in the field to maintain enhanced photosynthesis and therefore productivity as [CO2] continues to rise.